The fool, the hero and the sage: narratives of non-consumption as role distance from an urban consumer-self - Nixon, Elizabeth (Taylor & Francis, 2018)
One fruitful perspective with which to think differently about the consuming subject in affluent capitalist societies can be found in the field of non-consumption. Whilst ‘choices’ not to buy, own and use are often tacit in analyses of social class dynamics, identity expression, and consumer resistance, here we adopt the dramaturgical perspective of Erving Goffman to argue that forms of non-consumption may occur within expressions of role distance. Our interpretive analysis of interview narratives identifies three imagoes - the fool, the hero and the sage - that our informants reproduced to disaffiliate from a virtual self generated by participation in the shopping situations dominating many urban centres. We conclude that buying and consuming less in ‘everyday’ contexts may require the performance of alternative, culturally-available personas, and that role distance can signify alienation from a consumer role or, conversely, constitute a defence against actual attachment to it.